2010
DOI: 10.1007/s00125-010-1750-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-lowering agents and cancer mortality rates in type 2 diabetes: assessing effects of time-varying exposure

Abstract: Aims/hypothesis We explored the relationship between glucose-lowering agents and cancer mortality rates in type 2 diabetes patients, hypothesising a decreased risk of cancer mortality with metformin use and a dose-risk gradient for insulin therapy. Methods This was a population-based cohort study using administrative data from Saskatchewan Health, Canada. We identified new users of metformin or sulfonylureas from 1 January 1991 to 31 December 1996, with follow-up until death, departure from the province or 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 43 publications
3
125
1
2
Order By: Relevance
“…Recent observational studies have linked increasing insulin exposure with an increased risk of cancer incidence or increased cancer mortality rates [2,4,6,7]. As observational studies, they have a number of limitations and by themselves do not allow inference of causation.…”
Section: Epidemiological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observational studies have linked increasing insulin exposure with an increased risk of cancer incidence or increased cancer mortality rates [2,4,6,7]. As observational studies, they have a number of limitations and by themselves do not allow inference of causation.…”
Section: Epidemiological Datamentioning
confidence: 99%
“…This has been highlighted by observational studies suggesting a protective effect on cancer outcomes for metformin [1][2][3][4] and glitazones [5], but on the other hand a potential increased cancer risk associated with exogenous insulin [2,4,6,7], insulin analogues [8,9] and sulfonylurea therapies [2,4,7].…”
mentioning
confidence: 99%
“…In addition, studies report that glucoselowering treatments may modulate cancer risk but many of these pharmaco-epidemiological studies have methodological limitations. For this paper, we note that some studies on the relationship between treatments for diabetes and cancer risk report cancer incidence as the primary endpoint [2][3][4][5][6][7][8], while others report cancer mortality [9][10][11][12][13][14]-but are these two endpoints interchangeable? Here, we develop a conceptual framework within which to evaluate this question.…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based study including 11,876 patients with type 2 diabetes, Evans et al (26) reported a reduced incidence of cancer in patients treated with metformin, compared with patients not treated with metformin [odds ratio (OR), 0.79; 95% confidence interval (CI), 0.67-0.93]. Bowker et al (27) compared patients with type 2 diabetes in the metformin (monotherapy or combined) group and sulfonylurea monotherapy group, and reported that the cancer mortality rate was significantly decreased in the metformin group [hazard ratio (HR), 0.80; 95% CI, 0.65-0.98; P= 0.03), compared with the sulfonylurea group. In a study of 4,085 patients exhibiting type 2 diabetes, Libby et al (28) identified that the incidence of cancer in patients treated with metformin (7.3%) was significantly lower than that observed in patients treated with alternative drugs (11.6%).…”
Section: Effect Of Metformin On Carcinogenic Riskmentioning
confidence: 99%